2020
DOI: 10.1002/ldr.3697
|View full text |Cite
|
Sign up to set email alerts
|

Variation in soil geochemical properties and microbial communities in areas under land developed for educational use (university and other campuses)

Abstract: During land development, some important changes take place in the soil environment.Understanding these responses is of great significance for solving local and global environmental issues caused during land development. Till now, studies within education parks or university/college towns, especially inside and outside of a campus, were rarely reported. Herein, treating a campus as a semi-open and coupled system, we collected soil samples (109 sites) inside and outside of a campus to reveal the variation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These soil environmental changes can significantly affect the ecological processes and ecosystem multifunctionality of belowground systems, and thus soil organisms are also impacted. In this context, some previous studies have found that land degradation may significantly decrease the diversity of soil microbial communities [ 10 , 11 ]. Soil fauna is a critical component of soil organisms and has an irreplaceable role in the soil food web [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These soil environmental changes can significantly affect the ecological processes and ecosystem multifunctionality of belowground systems, and thus soil organisms are also impacted. In this context, some previous studies have found that land degradation may significantly decrease the diversity of soil microbial communities [ 10 , 11 ]. Soil fauna is a critical component of soil organisms and has an irreplaceable role in the soil food web [ 12 ].…”
Section: Introductionmentioning
confidence: 99%